Credit misallocation and macro dynamics with oligopolistic financial intermediaries - Alessandro T. Villa (Federal Reserve Bank of Chicago, 2022)
Bank market power shapes firm investment and financing dynamics and hence affects the transmission of macroeconomic shocks. Motivated by a secular increase in the concentration of the US banking industry, I study bank market power through the lens of a dynamic general equilibrium model with oligopolistic banks and heterogeneous firms. The lack of competition allows banks to price discriminate and charge firm-specific markups in excess of default premia. In turn, the cross-sectional dispersion of markups amplifies the impact of macroeconomic shocks. During a crisis, banks exploit their market power to extract higher markups, inducing a larger decline in real activity. When a "big" (i.e., non-atomistic) bank fails, the remaining banks use their increased market power to control the supply of credit, worsening and prolonging the recession. The results suggest that bank market power could be an important concern when formulating appropriate bail-out polices.
Keywords: D43; E44; G12; G21; L11; 330; Dynamic Financial Oligopoly; Endogenous Financial Markups; Heterogeneous Firms; Firm Dynamics; Micro-Founded Financial Frictions; Price Discrimination